(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Glaucoma is not only one of the most common, but also one of the most severe chronic and progressive eye diseases. Therefore, the disease is a relevant problem in ophthalmology and a leading cause of reduced vision and irreversible blindness. Purpose: To assess the incidence of glaucoma in the republic and the city of Tashkent, and predict disease incidence for the subsequent decade. Material and Methods: The report of the Ministry of Health “On the numbers of diseases and registered patients residing in the primary service area of the medical facility» and national statistical collections (“Statistical materials on the activities of healthcare institutions of the Republic of Uzbekistan”) for 2010-2019 were studied to determine the incidence of glaucoma and the relevant characteristics in the republic. Results: These materials allowed us to obtain the data on annual incidences of newly diagnosed cases and annual incidences of first visits of previously diagnosed cases of glaucoma in adults (i.e., individuals older than age 19) in the regions of the country for 2010 to 2019 years. The prediction of the incidence of glaucoma in the republic of Uzbekistan and the city of Tashkent necessitates organizational and treatment-and-diagnostic measures for combating the disease, these measures being of a social and medical importance.